Звук в індивідуальній поетичній картині світу Миколи Вінграновського - Іваненко, І. (Культура слова, 2019)
У статті проаналізовано моделі метафоричного опису
звуків, актуальні для індивідуальної поетичної картини світу
М. Вінграновського. Визначено, що найпродуктивніший тип
аудіальної метафоризації пов’язаний із вербалізацією асоціативно-
образних зв’язків «звук – природа». Її актуальність визначає
колективний (закріплений словесною традицією) та індивідуальний
(авторський) досвід сприймання «на слух» об’єктів національного
простору ріка, небо, вода, ліс, гай, дерева та пов’язаних із ними явищ
природи (вітер, буря, гроза, дощ) і живих істот (птахів, тварин,
комах). Стійкість мотивованих цим досвідом асоціацій у поезії
М. Вінграновського має послідовне підтвердження.
Доведено, що важливий фрагмент звукового окреслення світу в
ідіостилі автора становить образ тиша, який утворює семантичну
опозицію до образів із семою ‘звук’. Засвідчено естетичне
розгортання образу тиша в різноструктурних метафоричних
структурах: дієслівних предикативних, дієслівних об’єктних,
оксиморонних, тавтологічних.
Розглянуті аудіальні метафори підтверджують, що
естетизована вербалізація звукових вражень – одна з домінант
індивідуального поетичного фразотворення М. Вінграновського,
у мовотворчості якого метафори із семою ‘звук’ є незаперечними
художніми домінантами. The article analyzes models of metaphorical description of sounds that
are relevant to M. Vinhranovsky’s individual poetic picture of the world.
It is determined that the most productive type of audio metaphorization
is related to the verbalization of associative sound-to-nature relationships.
Its relevance is determined by the collective (secured by verbal tradition)
and individual (author) experience of perceiving objects of national space,
such as river, sky, water, forest, grove, trees, as well as related phenomena
of nature (wind, storm, thunder, rain). and living things (birds, animals,
insects). The persistence of associations in the poetic texts motivated by
this experience has been consistently confirmed.
The collective and individual experience of perception of the
phenomena of the nature of rain, thunderstorm, rain, wind, water
motivates the active use of «sound» verbs, which metaphorize the various
actions and intensity of manifestation of these phenomena.
The stylistic performance of common linguistic formulas with
stylistically neutral verbs - carriers of the archives of ‘sounds of nature’
is traced.
It is proved that an important fragment of the sound definition of the
world in the national linguistic-poetic practice and in the idyllic style
of M. Vinhranovsky as its symbolic fragment is the image of “silence”.
Updating the “zero” manifestation of audio semantics, it creates a semantic
opposition to images with the seven “sound”. The aesthetic unfolding of
the image of silence in various structural metaphorical structures: verbal
predicative, verbal object, oxymoronic, tautological is attested.
Analyzed metaphors confirm that the aesthetized verbalization
of sound impressions is one of the dominants of M. Vinhranovsky’s
individual poetic phrase, in which the metaphors with the seven ‘sound’
are indisputable artistic dominants.